Influence of high levels of zinc from zinc oxide, zinc sulfate, or a zinc amino acid complex on starter pig performance - J C Woodworth; P R O'Quinn; J A Loughmiller; S A Moser; T M Fakler; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1998)
Three hundred and sixty early-weaned barrows were fed either a control diet; diets containing added Zn (l00, 200, 300, 400, or 500 ppm) from zinc sulfate or a zinc amino acid complex (AvailaZn); or a diet containing 3,000 ppm of additional Zn from zinc oxide. All diets contained 165 ppm of Zn from zinc oxide from the trace mineral premix. Pigs fed 3,000 ppm of Zn from zinc oxide had maximum growth performance compared to those fed other diets, whereas those fed added zinc sulfate and AvailaZn showed intermediate results relative to the negative control and the 3,000 ppm of Zn from zinc oxide diet. These results support previous Kansas State University research showing maximum performance being achieved with additions of 3,000 ppm of Zn from zinc oxide. Further research is needed to evaluate the intermediate response to zinc sulfate and AvailaZn and determine whether the benefits in ADG and F/G were due to a growth promotion response or whether the starter pig has a higher Zn requirement than met by the negative control (165 ppm Zn from zinc oxide).; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Early-weaned pigs; Growth; Zinc